A clinical assay for reactive oxygen species – ready for primetime?. Issue 1 (January 2018) - De Jonge, Christopher J.
Abstract: Reactive oxygen species (ROS) have been demonstrated to have damaging effects on human sperm function. The measurement of ROS as an adjunct to traditional semen analysis has clinical relevance as part of the diagnosis of male infertility. The assay best suited to the clinical laboratory environment for detecting ROS generation remains somewhat controversial. A recent report on a multicenter study evaluating the reduction of nitroblue tetrazolium (NBT) to formazan precipitate as an indirect reporter of ROS-generating activity in spermatozoa, seminal plasma and semen has received a critique raising questions as to the sensitivity and specificity of the assay for detecting ROS. The authors of the report argue in response that the assay has validity and yields results that are potentially clinically significant. This dialogue serves to (re)direct readers to the original article and to consider carefully the intent and potential application of the assay, and whether there is sufficient scientific evidence to judiciously support its clinical diagnostic application.